2021
DOI: 10.1126/science.abg0492
|View full text |Cite
|
Sign up to set email alerts
|

Extreme oxidant amounts produced by lightning in storm clouds

Abstract: Lightning increases the atmosphere’s ability to cleanse itself by producing nitric oxide (NO), leading to atmospheric chemistry that forms ozone (O3) and the atmosphere’s primary oxidant, the hydroxyl radical (OH). Our analysis of a 2012 airborne study of deep convection and chemistry demonstrates that lightning also directly generates the oxidants OH and the hydroperoxyl radical (HO2). Extreme amounts of OH and HO2 were discovered and linked to visible flashes occurring in front of the aircraft and to subvisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
6

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(76 citation statements)
references
References 60 publications
4
66
6
Order By: Relevance
“…During the DC3 field campaign enhanced HO x was measured, usually with little corresponding enhanced LNO x or electrical activity detected in the volume of air that the aircraft flew through (Brune et al, 2021). These experiments confirm the observation that LHO x can be generated in weak, subvisible discharges, with little to no detectable NO x present.…”
Section: Subvisible Electrical Dischargessupporting
confidence: 70%
See 4 more Smart Citations
“…During the DC3 field campaign enhanced HO x was measured, usually with little corresponding enhanced LNO x or electrical activity detected in the volume of air that the aircraft flew through (Brune et al, 2021). These experiments confirm the observation that LHO x can be generated in weak, subvisible discharges, with little to no detectable NO x present.…”
Section: Subvisible Electrical Dischargessupporting
confidence: 70%
“…However, previous studies have shown that the differences in LNO x production between different discharge types is mostly due to differences in current and how long the discharge lasts (Cooray et al, 2009 et al, 2011), and information on both of those variables has been provided in this work. Additionally, both AC and DC pulses can interact with atmospheric gases in the same way (Raizer, 1997), making the AC discharges used in this study suitable for reproducing the discharges encountered during the DC3 field campaign, which were typically the weaker anvil discharges and not the strong high-current lightning (Brune et al, 2021). As a test, we used DC pulses from a Marx generator also to make sparks and found that comparable values for LNO x and LHO x were produced for weak currents from both devices.…”
Section: Laboratory Setupmentioning
confidence: 99%
See 3 more Smart Citations